ON THE FIRST NON-TYPE LOCALITY FINDING OF DUVALIUS (PARADUVALIUS) STANKOVITCHI GEORGEVITCHI (JEANNEL, 1923) (COLEOPTERA: CARABIDAE: TRECHINAE) (Acta Entomologica Serbica, 2019)
Troglobitic trechine ground beetle, Duvalius (Paraduvalius) stankovitchi georgevitchi (Jeannel, 1923) was found outside its type locality (Lazareva Pećina Cave, village of Zlot, near Bor, Kučajske Planine Mts., eastern Serbia) for the first time. Specimens of the mentioned taxon were recently collected in Vernjikica Cave nearby. Morphological and molecular analyses confirmed that specimens from both caves belong to the same subspecies, and that there are no significant differences between them.